Perlindungan Hukum Atas Wartawan Saat Melakukan Penyelidikan Kasus Ditinjau Dari Undang-Undang Pers - Arnezul Achmad Satriawan; Klarisa Tabita Khenina Tarigan; Bombong Munif Musyaffa’ Priambodo (Indonesian Journal Publisher, 2026)
Violence against journalists continues to occur in Indonesia despite the guarantee of press freedom under Law No. 40 of 1999 concerning the Press. This study aims to examine the forms of legal protection available to journalists and analyze the fulfillment of criminal law elements in cases of violence against them, using the case of Rico Pasaribu, a journalist for TribrataTV in Karo Regency, as a reference. The research employs a normative juridical method by analyzing statutory regulations, legal doctrines, and relevant legal materials related to press freedom and criminal responsibility. These materials are examined qualitatively to assess the framework and its implementation in practice. The findings indicate that although press freedom is legally recognized, law enforcement related to crimes against journalists remains weak. Data from 2023 to 2024 show that 148 cases of violence against journalists occurred in Indonesia, reflecting a gap between legal guarantees and their actual protection. The case of Rico Pasaribu illustrates how journalists remain vulnerable due to ineffective enforcement mechanisms and the lack of consistent deterrent measures against perpetrators. This study concludes that the core problem lies not in the absence of legal regulation, but in insufficient enforcement of existing laws.